How risky debt became ordinary: A practice theoretical approach. (May 2020) - Pellandini-Simányi, Léna; Vargha, Zsuzsanna
Existing research on how consumers experience increasing debt as normal focuses on the shifting moral meanings surrounding debt. Examining rapid mortgage debt escalation in post-socialist Hungary, we propose a different approach. Using practice theory, we identify credit use as 'ordinary consumption': a non-expressive practice which enables other, meaningful practices; akin to energy use. Like energy, credit is channelled by background infrastructures, such as mortgage instruments. We find that mortgage debt grew and became 'naturalized' through the co-evolution of practices associated with a 'normal life' centred on the home on the one hand, and of available mortgage instruments on the other. This process did not change what debt means but stripped its meanings, making debt increasingly unreflected and invisible. We argue that this invisibility is not a natural characteristic of mortgages but a contested quality. High-risk mortgages became invisible through particular selling devices and discourses that positioned mortgages as 'expert goods', to be preselected and installed by qualified advisers. Emphasising the socio-material structuring of this process, we conclude by integrating the meaning-laden and unreflected credit practices into a new theoretical framework, as contingent qualities of credit consumption.